Does longitudinal or transverse orientation of the ultrasound probe improve cannulation success in minimally invasive venous surgery: A multicentre randomised controlled trial. (October 2020) - Aherne, Thomas M; Zafar, Adeel S; Gourlay, Daniel; O'Neill, Damien C; Bashar, Khalid; Yap, Charyl JQ; Tang, Tjun Y; Walsh, Stewart R
Objective: This study evaluates the effect of transverse and longitudinal ultrasound transducer orientation on saphenous vein cannulation during endovenous ablation. Methods: A single-blinded, multicentre, randomised controlled trial was performed in patients undergoing ultrasound-guided venous cannulation for saphenous ablation. The primary outcomes were overall cannulation success and time to successful cannulation. Results: In total, 100 patients were assigned to parallel longitudinal orientation and transverse orientation groups. Cannulation success was 100%. There was no significant variation in time to cannulation detected between the transverse orientation and longitudinal orientation (85 s vs. 71 s, p = 0.314). Longitudinal orientation was associated with significantly fewer needle passes [median 3 (interquartile range 1–5) vs. 2 (interquartile range 1–3), p = 0.026] and less pain (median visual analogue scale score 1 vs. 2.5, p = 0.039) than those in the transverse orientation group. Conclusion: This trial has shown that while longitudinal orientation is associated with less procedural pain it has no significant effect on time to target vein cannulation during endovenous ablation.